Gut microbiota in alcohol-related liver disease: pathophysiology and gut-brain cross talk - Zhu, Lin; Wang, Yixuan; Pan, Calvin Q.; Xing, Huichun (Frontiers in Pharmacology, 2023)
Alcohol-related liver disease (ALD) from excessive alcohol intake has a unique gut microbiota profile. The disease progression-free survival in ALD patients has been associated with the degree of gut dysbiosis. The vicious cycles between gut dysbiosis and the disease progression in ALD including: an increase of acetaldehyde production and bile acid secretion, impaired gut barrier, enrichment of circulating microbiota, toxicities of microbiota metabolites, a cascade of pro-inflammatory chemokines or cytokines, and augmentation in the generation of reactive oxygen species. The aforementioned pathophysiology process plays an important role in different disease stages with a spectrum of alcohol hepatitis, ALD cirrhosis, neurological dysfunction, and hepatocellular carcinoma. This review aims to illustrate the pathophysiology of gut microbiota and clarify the gut-brain crosstalk in ALD, which may provide the opportunity of identifying target points for future therapeutic intervention in ALD.